INSTAGRAM AS A DIGITAL PREACHING MEDIA: A CASE STUDY OF QURANREVIEW - Putri, Tamara Maylyana (Universitas Islam Negeri Mataram, 2025)
The development of information technology today gives birth to new communication patterns and becomes a forum for innovation in da'wah communication, such as the utilization of Instagram by the Quranreview account contextually has actual issue content through the Qur'anic interpretation approach. The purpose of this study is to analyze Quranreview in overcoming da'wah challenges and strengthening arguments related to digital da'wah innovation. This research uses qualitative methods with interview techniques, observation and content analysis. The results of the study are Quranreview explains that current phenomena are always related to the Qur'an, the use of Quranreview's visual design is stressing the interest of followers, light language makes the delivery of digital da'wah easy to understand and live by.